TECHNOLOGY READINESS INDEX OF MICRO-ENTREPRISES USING LOCAL E-COMMERCE IN SPECIAL REGION OF YOGYAKARTA - Saputra, Ahmad Meidy; Ayuningtyas, Tania Nugraheni; Saputra, Dani Setiadi (J-MIND (Jurnal Manajemen Indonesia), 2025)
Technology readiness is a crucial aspect in encouraging local e-commerce adoption by micro-entreprises. This study aims to analyze the technological readiness of Sibakul Market-Hub in the Special Region of Yogyakarta using the Technology Readiness Index (TRI). The study population was 100 micro-entreprises with snowball sampling techniques, analyzed through validity, reliability, and TRI based on optimism, innovativeness, discomfort, and insecurity. The results showed an average TRI of 3.13 with medium technology readiness (72%), driven by the highest optimism (4.05), Innovativeness (3.69), but hampered by insecurity (2.50) and discomfort (2.29). These findings have strategic implications for Micro-entreprises digitalization policies through collaborative government-platform interventions for sustainable transformation.